Eigen Radio Frequency Signals Localized at Alfven Resonances in A Tokamak Scrape-Off Layer - Trush, Oleksandr; Girka, Igor; Tierens, Wouter (East European Journal of Physics, 2025)
Eigen electromagnetic waves with small toroidal wave indices and positive poloidal wave indices are considered in the Ion Cyclotron Range of Frequencies (ICRF) in a tokamak Scrape-Off Layer (SOL). The waves are shown theoretically to exist in the form of the signals localized at the local Alfven Resonances (ARs). The evanescent regions in the direction of lower plasma density are provided by the presence of the wave nonzero poloidal wave indices. The narrow evanescent regions in the direction of higher plasma density are caused by strong plasma variation. The latter regions separate ARs from the high-density SOL and plasma core which are propagating regions for ICRF waves. The dispersion relation of ICRF signals is derived analytically and solved numerically. Possible relevance of the obtained results to experimental measurements is discussed. An exhaustive definition of the signals’ excitation sources is out of scope of the present study.